International reserves and the composition of equity capital inflows - Xingwang Qian; Andreas Steiner (Osnabrück University, Institute of Empirical Economic Research, 2012)
We study the effect of central banks' international reserve hoardings on the composition of equity capital inflows, namely the ratio of portfolio equity investment (PEI) to foreign direct investment (FDI). Foreign investors' decisions regarding the location and the type of equity capital investment might be influenced by a country's level of international reserves. In a simple theoretical model, we show that higher reserves, thanks to their ability to lower exchange rate risk, reduce the risk premium of portfolio equity inflows. Hence, higher reserves are expected to increase the inflow of portfolio equity investment relative to FDI. We test this hypothesis for a sample of emerging markets during the period 1980-2007 using static and dynamic panel data methods. The results suggest that higher levels of reserves are associated with a larger ratio of PEI inflows relative to FDI. This result points to a collateral benefit of reserves that has been neglected so far: Reserves contribute to deeper domestic financial markets and facilitate domestic firms' access to foreign financing.
Keywords: F3; F4; 330; international reserves; capital inflows; equity capital